2016
DOI: 10.1038/srep34729
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics and Complicated Genetic Transmission Network Patterns of HIV-1 CRF01_AE among MSM in Shanghai, China

Abstract: To explore the evolutionary dynamics and molecular transmission patterns of HIV-1 CRF01_AE in depth among men who have sex with men (MSM) in Shanghai, we constructed phylogenetic tree and genetic transmission networks based on 1, 152 pol sequences from MSM, 282 from other risk groups and 795 references. Phylogenetic analyses identified two distinct major CRF01_AE lineages and a Shanghai-based sub-lineage. The estimated tMRCAs for lineage 1 and 2 were 1996.0 (1992.9–1999.2) and 1997.8 (1994.3–2001.4), respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 33 publications
7
40
1
Order By: Relevance
“…We observed that individuals with multiple links represented only a minority of persons but were involved in most of the persons in network. This result was similar to our previous results in Shanghai and confirmed that a few ‘core population’ indeed drive transmission networks to a significant extent 9. Identifying and controlling these ‘core population’ is therefore crucial for curbing HIV spread in a population 24 25.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We observed that individuals with multiple links represented only a minority of persons but were involved in most of the persons in network. This result was similar to our previous results in Shanghai and confirmed that a few ‘core population’ indeed drive transmission networks to a significant extent 9. Identifying and controlling these ‘core population’ is therefore crucial for curbing HIV spread in a population 24 25.…”
Section: Discussionsupporting
confidence: 90%
“…w6 Several studies indicated that migrants accounted for a large proportion of HIV epidemic in China 16, w7 and posed a persistent increase among newly diagnosed HIV infections every year in some areas 4 16 26. Our previous observation suggested ongoing transmission of CRF01_AE strain between Shanghai city and other provinces, for which migrants played a crucial role 9. In this in-depth observation at national level, we expanded the number of available sequences and revealed that large-scale population migration between China’s provinces undoubtedly facilitated viral transmission.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations